The origin of the political : Hannah Arendt or Simone Weil? - Esposito, Roberto, 1950- (Commonalities., 2017)
This work explores the conceptual trajectories of two of the twentieth century's most vital thinkers of the political: Hannah Arendt and Simone Weil. Taking Homer's Iliad as the common origin and point of departure for our understanding of Western philosophical and political traditions, the text examines the foundational relation between war and the political.